Analisis Pengetahuan Mahasiswa Tadris Biologi UINSU Terhadap Artikel Jurnal Ilmiah - Nur Afinni, Ummi; Silvia, Condy; Amirah, Nurul; Fachrizal, Ahmad (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of this study was to find out how far UINSU biology tadris students know scientific journal articles, and see how far UINSU biology tadris students understand scientific journal article writing. The research method used in this study was descriptive qualitative. The population in this study were UINSU biology students. And the samples in this study were UINSU biology students class 2019-2022, namely 40 students who were still actively studying. The data collection technique used is the survey method. The sampling technique used in this study was random sampling. The data analysis technique was then processed using a descriptive analysis method to find out the results of a questionnaire conducted on Tadris Biology UINSU students class of 2019-2022. The results of this study are based on informants namely students that many students have made scientific journal articles and that means that many students understand scientific journal articles, both in terms of searching for scientific journal articles, understanding scientific journal articles and even making articles. scientific journals. But behind that there are also students, especially in the class of 2022, who still produce few scientific journal articles, and sometimes it's even difficult to find and understand them. Keywords: Understanding Analysis, Scientific Journal Articles, Tadris Biology Study Progra